Ethanol Extract Burn Gel Formulation of Bay Leaves (Syzygium polyanthum (Wight.) Walp.) - Dwi Ayu Andini, Annisa; Simanullang, Gayatri; Damayanti Abdul Karim, Dewi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Burns are skin tissue damage caused by hot objects or hot liquids. One of the potentially healing plants for burns is the bay leaves (Syzygium polyanthum (Wight.) Walp.). Bay leaves ethanol extract contains flavonoids known for their anti-inflammatory properties, which can aid in wound healing. This study aimed to determine the formulation and effectiveness of a gel made from ethanol bay leaves extract. Bay leaves were extracted using the maceration method with a 70% ethanol solvent; then, its extract was formulated into gel preparations. Following the formulation,the researchers conducted physicochemical evaluations and burn effectiveness trials using New Zealand albino rabbits. The research results indicated that the burn gel formulations with 3% and 6% concentration variations exhibited favourable physical properties, including organoleptic, homogeneity, and pH from 5.33 to 5.8, spreadability from 4.77 to 5.55 cm, adhesion strength from 5.47 to 11.6 seconds, and viscosity ranged from 12.507 to 16.080 cPs. The 15-day burn effectiveness test revealed no significant differences, indicating that the reduction in wound diameter was relatively consistent across all test groups. The percentages of wound healing in the negative control, bioplacentone, F1, and F2 were 42.48%, 54.73%, 43.84%, and 65.89%, respectively. Therefore, F2 demonstrated the best wound-healing performance.